The influence of heregulins on human Schwann cell proliferation - Levi, AD (J Neurosci, 1995)
The use of Schwann cell (SC) autotransplantation to influence neural repair in humans is dependent upon identifying mitogens that will effectively expand human Schwann cells (SCs) in culture. The recent purification and molecular cloning of glial growth factor (GGF), a potent mitogen for rat Schwann cells, has led to the recognition that a family of proteins (GGF/HRG/NDF/ARIA) are alternatively spliced products of a single gene. The heregulins (HRGs) have been characterized with respect to their influence on human breast cancer cell lines; here we examined whether the HRGs have mitogenic activity for human SCs. Using DNA synthesis assays and serial passaging of cells in culture, we demonstrate that HRG is an effective mitogen for human SCs and that, in the presence of agents that elevate cAMP, it is possible to expand these cells over multiple passages without overwhelming fibroblast contamination. One putative target for this family of proteins is p185erbB2, and EGF-like receptor tyrosine kinase that is encoded by the erbB2 protooncogene. In this report we also demonstrate that the erbB2/3/4 messages as well as the erbB2/3 receptor proteins are present within cultured human SCs. The addition of HRG to human SCs results in tyrosine phosphorylation of a 185 kDa protein. In the presence of stimulatory concentrations of HRG, a blocking monoclonal antibody (2C4) to p185erbB2 is capable of significantly inhibiting phosphorylation of a 185 kDa protein as well as the subsequent incorporation of 3H-thymidine within the human SC. These latter results implicate an important role for p185erbB2 in mediating the mitogenic response of human SCs to HRGs.